Review and prospect of genetic transformation in turfgrasses - CHAI Ming-liang; WANG He-fei (浙江大学学报. 农业与生命科学版)
During the past two decades, substantial progress has been made in genetic modification of turfgrasses. The systems for genetic transformation have been established in most of the main turfgrass species, and the induction of resistant genes into the species has been becoming the hotspot. The factors affecting the genetic transformation of turfgrasses, and the problems existing in the course of transformation, i.e., somaclonal variation and the stabilization in the transgenic plants, the efficiency of genetic transformation, the effect of foreign genes on the environment were summarized, the relationship between genetic transformation and traditional breeding was discussed and the research aims for turfgrass breeding in the future were pointed out.